Strengthening the maqasid al-shariah contents in undergraduate quantity surveying programme at KAED,IIUM - Mohd Fauzi, Puteri Nur Farah Naadia; Ahmad Sarkawi, Azila; Abdul Rashid, Khairuddin (2015)
Quantity Surveying is among the key professions that are involved in the provision of services related to the built environment. Quantity Surveyors provide services in the critical areas of procurement, estimating, contract documentation and post contract administration of construction projects and built assets. In the context of Islamization of human knowledge (IoHK), recent studies suggest that the Bachelor in Quantity Surveying Programme (BQS) (Honours) at the Kulliyyah of Architecture and Environmental Design (KAED), International Islamic University Malaysia (IIUM) has content that include the five key components of the maqasid al-shariah namely preservation of (i) faith, (ii) self, (iii) intellect, (iv) lineage, and (iv) property. However, the studies also indicate that the programme’s maqasid al-shariah contents appear to be un-evenly distributed with “faith” and “lineage” being the weakest while “intellect” is the highest. Consequently, efforts are being made in attempting to achieve a more balanced programme. This paper reports on a study to seek ways on how to achieve a more balanced BQS (Honours) programme at KAED, IIUM in the context of the maqasid al-shariah. The study focusses to propose contents of the BQS (Honours) programme courses in order to increase the “faith” and “lineage” components therein and employed a combination of literature review, content analysis of the programme structure and course outlines of the BQS (Honours) programme at KAED, IIUM and a series of detail discussions among BQS lecturers. Key findings from the study suggest that the BQS (Honours) programme at KAED IIUM has potentials towards achieving a more balanced maqasid al-shariah among the five key components and the types of courses and topics to be incorporated into the programme have been identified. The research outcome, if appropriately applied, would facilitate preparing graduates with the necessary knowledge and understanding of the maqasid al-shariah within the field of quantity surveying. This therefore should facilitate them in performing their roles as professionals related to the built environment and as the Earth’s khalifah.